The effects of protein supplementation on performance of beef cattle grazing native mixedgrass range in western Kansas - McMullen, Carson (Kansas State University, 2015)
Cattle consuming low-protein forage (<7% CP) require additional supplemental protein to maintain BW and BCS. Daily delivery of protein supplements places undue financial burden on cattle producers. Supplementing cows as infrequently as once every 6 d) has resulted in similar changes cow BW and BCS when compared to daily supplementation. As calving season nears, producers may wish to increase supplementation frequency. The responses to a change in supplementation frequency during the third trimester of gestation have not been widely investigated. Therefore, our objective in Study 1 was to evaluate the effect of altering supplementation frequency during late gestation on performance of spring-calving cows grazing low-quality, dormant native range and supplemented with dried distillers grains with solubles (DDG). Angus × cows (n = 238; mean age = 6 ± 2.5 yr; average initial BW = 618 ± 56.2 kg; average initial BCS = 5.7 ± 0.03) were stratified by age, BW, BCS, and assigned randomly to 1 of 4 treatments: 1) DDG daily (D1); 2) DDG once every 6 d (D6); 3) DDG daily from d 1 to d 60 and then every 6 d (D1-D6); 4) DDG every 6 d from d 1 to d 60 and then daily (D6-D1). Treatments were initiated 100 d prior to expected onset of calving. Cow BW and BCS were measured every 28 d. Cows were sorted daily before supplementation at 0830 h. Supplement delivery was calculated to meet dietary CP requirements. Increasing supplementation frequency 28 d prepartum negatively affected final BW and BW change from d 61-88 for the D6-D1 supplementation group (P < 0.05) compared to other supplementation groups. Cow BW change for the study (d 1-88) was also less (P < 0.02) for the D6-D1 group compared to other groups but was also affected (P < 0.01) by year. Under the conditions of our study, increasing supplementation frequency 28 d before calving was not a viable means of increasing prepartum cow performance. The development of replacement heifers is a significant expense for cow-calf producers. Reducing the cost of heifer development programs while achieving high pregnancy rates is an industry-wide goal. Therefore, our objective in Study 2 was to determine if DDGS was a viable replacement for an oilseed meal-based protein supplement when developing heifers on low-quality, dormant native range. Treatments consisted of daily supplementation of either 1.65 kg DM DDG (DDG; 0.57 kg CP) or 1.37 kg DM of a 73.6% soybean meal and 26.4% rolled sorghum grain mixture (SBM-S; 0.56 kg CP). Treatments were administered from 1/15 until 4/8 (84 d). Initial BW and BCS were not different between treatments (P ≥ 0.29). Final BW and BCS also did not differ (P ≥ 0.55) between treatments; moreover, rates of BW and BCS change were not different (P ˃ 0.30) between treatments. Proportions of heifers pubertal before ovulation synchronization, first service conception rates, and final pregnancy rates were not affected (P > 0.40) by treatment. Under the conditions of our study supplemental CP fed at a rate of approximately 0.56 kg daily was sufficient to promote growth and BCS change adequate for optimal reproductive performance; moreover, supplement ruminal degradability of CP did not influence heifer performance over an 84-d development period.
Keywords: Dried distillers grain; Low-quality forage; Protein supplementation; Heifer performance; Cow performance; Soybean meal; Animal Sciences (0475)